Cardiac biomarkers in blood, and pericardial and cerebrospinal fluids of forensic autopsy cases: A reassessment with special regard to postmortem interval. Issue 5 (September 2015) - Chen, Jian-Hua; Inamori-Kawamoto, Osamu; Michiue, Tomomi; Ikeda, Sayuko; Ishikawa, Takaki; Maeda, Hitoshi
<x xml:space="preserve">Abstract</x> Highlights Previous studies on postmortem cardiac biomarkers described inconsistent results. This study comprehensively reviewed autopsy data with regard to cause of death. Cardiac biomarker levels depended on the causes of death and postmortem time. Elevated cardiac biomarker levels were not specific for myocardial infarction. Other causes of elevated cardiac biomarkers were similar to clinical findings.